2013
DOI: 10.4140/tcp.n.2013.361
|View full text |Cite
|
Sign up to set email alerts
|

Appropriateness of Medication Prescribing Using the STOPP/START Criteria in Veterans Receiving Home-Based Primary Care

Abstract: A statistically significant decrease in the STOPP score was found. Although the START score increased, the change was not found to be statistically significant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 14 publications
1
20
0
Order By: Relevance
“…The use of STOPP/START criteria in improving health care outcomes in primary care, remains to be established. However, recent findings in secondary care may be promising [28][30]. It has been argued that primary care pharmacists may overestimate the rate of PIM and underestimate the rate of PPO when using STOPP and START criteria due to lack of clinical information [14].…”
Section: Discussionmentioning
confidence: 99%
“…The use of STOPP/START criteria in improving health care outcomes in primary care, remains to be established. However, recent findings in secondary care may be promising [28][30]. It has been argued that primary care pharmacists may overestimate the rate of PIM and underestimate the rate of PPO when using STOPP and START criteria due to lack of clinical information [14].…”
Section: Discussionmentioning
confidence: 99%
“…One such criteria is the “Screening Tool to Alert doctors to the Right Treatment and the Screening Tool of Older Persons’ potentially inappropriate Prescriptions” (START/STOPP) Criteria. This tool goes a step further from the Beers list in addressing medications possibly indicated for older adults, as well as expanding on those that should be taken away [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…The START/STOPP criteria were used to comprehensively evaluate the appropriateness of medication regimens in older adults in a study by Brahmbhatt et al [ 8 ]. While this study found a significant reduction in the STOPP score between initial and follow up medication reviews, it did not find a significant increase in the START score.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Adverse drug reactions include a negative reaction to pharmacotherapy including confusion, depression, constipation, falls, fractures, delirium, possible hospitalization, and mortality (Cahir et al, 2010;Shahezwan, 2012;Hamilton, 2009;Brahmbhatt, Palla, Kossifologos, Mitchell, and Lee, 2013;Pretorius et al, 2013). Potentially inappropriate medications may be detected with a medication review (Hamilton, Gallagher, O'Mahony, 2009;O'Sullivan, O'Mahony, Parsons, Murphy, Patterson, Byrne, 2013).…”
Section: Theoretical Frameworkmentioning
confidence: 99%